Penguatan Political Awareness Kader Partai melalui Model Baddeley–James Berbasis ABCD dalam Membangun Perilaku Politik Bijak di Kabupaten Kerinci - ahmad, jafar; wafi, Mahmud Hibatul; Firmanda, Hengki; Handican, Rhomiy; Hayat, Ade Putra; Prasetia, Agung Tri; Saputra, Syukron; Nurzen, Nurzen (Institut Agama Islam Negeri Kerinci, 2025)
This community engagement program aims to strengthen the political awareness of party cadres through the integration of the Baddeley–James model and the Asset-Based Community Development (ABCD) approach in Kerinci Regency. The primary issue addressed is the limited analytical capacity of cadres in understanding power dynamics, alongside suboptimal ethical political behavior. A participatory method was employed using the ABCD cycle (discovery, dream, design, define, and destiny), combined with training in reading and carrying skills. The results indicate significant improvements in political understanding, active participation, and behavioral transformation toward more critical, reflective, and ethical political practices. Participants were also able to apply these competencies in field activities, particularly in capturing public aspirations and formulating policy recommendations. Furthermore, the program produced a training module and an ABCD-based political awareness model with replication potential. These findings highlight that integrating cognitive and participatory approaches is effective in fostering political behavior transformation and strengthening substantive local democratic practices